THE INFLUENCE OF DEAD LAYER EFFECT ON THE CHARACTERISTICS OF THE HIGH PURITY GERMANIUM P-TYPE DETECTOR - NGO , QUANG HUY (Nuclear Science and Technology, 2011)
This work presents an overview of the studies of the influence of dead layer effect on the characteristics of a high purity germanium (HPGe) p-type detector, obtained by the author and his colleagues in the recent years. The object for study was the HPGe GC1518 detector-based gamma spectrometer of the Center for Nuclear Techniques, Ho Chi Minh City. The studying problems were: The modeling of an HPGe detector-based gamma spectrometer using the MCNP code; the method of determining the thickness of dead layer by experimental measurements of gamma spectra and the calculations using MCNP code; the influence of material parameters and dead layer on detector efficiency; the increase of dead layer thickness over the operating time of the GC1518 detector; the influence of dead layer thickness increase on the decrease of detector efficiency; the dead layer effect for the gamma spectra measured in the GC1518 detector.